Peran Bimbingan dan Konseling Dalam Mengatasi Permasalahan Pada Siswa di MI Muhammadiyah Wonosobo - Agustina, Neli; Junaidah, Emy; Solihin, Rahmat (STAI Asy-Syukriyyah, 2024)
The role of guidance and counseling is very important in the world of schooling. In carrying out this role, of course there are obstacles and problems that occur from both internal and external factors. This research uses a descriptive qualitative method approach. By collecting data through observation, documentation and interviews in the field. Based on the results of observations, it was found that at MI Mummadiyah there were students who could not read well or were not fluent in reading, this was because students did not participate in teaching and learning activities well and effectively. The delay in students' ability to read from their friends is due to environmental conditions. Teachers' efforts to overcome this are to improve learning to read, providing facilitation either at home or at school for reading. After carrying out these efforts, it was found that students who were lagging behind in their reading skills were finally able to overcome them and keep up with their other friends who read fluently.